COMPARATIVE STUDY OF RUSSIAN AND TATAR PROVERBS AND PROVERBAL PHRASES WITH AN ELEMENT OF COMPARISON - I.A. Fedorova; L.R. Mingatina (Многоязычие в образовательном пространстве)
The article is devoted to the study of stable expressions with an element of comparison at the grammatical, lexical and syntactic levels. The purpose of the study is a comparative analysis of paroemias, such as proverbs, sayings, phraseological units in the Russian and Tatar languages and their lexical and grammatical characteristics. The relevance of the work lies, firstly, in the important role of proverbs as a means for comparing the mentality and culture of different peoples; secondly, in the need to study proverbial expressions as an important component of the unit of language that adds richness and expressiveness to our speech; thirdly, the study of figurative comparisons and their contrastive study in two languages indicates the belonging of people to a particular culture. 100 Russian and 100 Tatar proverbs and sayings, selected by a continuous sampling method from the dictionaries of K.R. Galiullin “The Language of Tatar folklore” and V. Dahl “Proverbs and Sayings of the Russian people,” were used in the study. The conducted analysis includes the sources of proverbs and sayings, identification of five main structural models of the studied paroemias in the Russian and Tatar languages, description of their similarities and differences. As a result of the study, the similarity of grammatical constructions of proverbial expressions in two differently structured languages was established, a thematic classification of the entire corpus of examples was made and the quantitative ratio of proverbs of the Russian language was determined by analogy with the Tatar language at the level of semantics. The main result of the analysis is an integrated presentation of the comparative area of the Tatar language and culture through the prism of the Russian language and culture.